Mapping the security arrangements for Khayelitsha's schools: what are the normative and functional outcomes of a nodal policing approach to poling school-based violence in Khayelitsha? - Henderson, Ashleigh (Department of Public Law, 2015)
In light of the contextual realities of school violence, the aim of this paper is to provide an analytical map of the security arrangements at schools in a particular area, namely Khayelitsha. The question is not whether these arrangements are failing (as will be made clear by the evidence provided in chapter four) but rather why and how they are failing. The task of identifying these gaps in an accurate and sufficiently nuanced way would be impossibly large if the scope of the study were all schools in South Africa. Furthermore, in order to be able to make precise recommendations and implement effective interventions, it is necessary to have a thorough understanding of the particular issues faced by particular schools, rather than schools in general. As such, I have chosen to narrow the scope of the study to one area where violence in schools has been shown to be particularly prevalent. The area in question is a large township located on the outskirts of the City of Cape Town called Khayelitsha. This area has been chosen not only to narrow the scope of the study, but also because policing in Khayelitsha has recently been the topic of an extensive Commission of Inquiry.